Integrative single-cell RNA and ATAC sequencing reveals that the FOXO1-PRDX2-TNF axis regulates tendinopathy - Guo, Junfeng; Tang, Hong; Huang, Pan; Ye, Xiao; Tang, Chuyue; Shu, Zhao; Guo, Junfeng; Kang, Xia; Shi, Youxing; Zhou, Binghua; Liang, Taotao; Tang, Kanglai (Frontiers in Immunology, 2023)
Tendinopathy, the most common form of chronic tendon disorder, leads to persistent tendon pain and loss of function. Profiling the heterogeneous cellular composition in the tendon microenvironment helps to elucidate rational molecular mechanisms of tendinopathy. In this study, through a multi-modal analysis, a single-cell RNA- and ATAC-seq integrated tendinopathy landscape was generated for the first time. We found that a specific cell subpopulation with low PRDX2 expression exhibited a higher level of inflammation, lower proliferation and migration ability, which not only promoted tendon injury but also led to microenvironment deterioration. Mechanistically, a motif enrichment analysis of chromatin accessibility showed that FOXO1 was an upstream regulator of PRDX2 transcription, and we confirmed that functional blockade of FOXO1 activity induced PRDX2 silencing. The TNF signaling pathway was significantly activated in the PRDX2-low group, and TNF inhibition effectively restored harmful cell degradation. Thus, we revealed an essential role of harmful cells in tendinopathy and proposed the FOXO1-PRDX2-TNF axis is a potential regulatory mechanism for the treatment of tendinopathy.